2021
DOI: 10.1155/2021/9066938
|View full text |Cite
|
Sign up to set email alerts
|

Anti-influenza A Virus Effects and Mechanisms of Emodin and Its Analogs via Regulating PPARα/γ-AMPK-SIRT1 Pathway and Fatty Acid Metabolism

Abstract: The peroxisome proliferator-activated receptor (PPAR) α/γ-adenosine 5 ′ -monophosphate- (AMP-) activated protein kinase- (AMPK-) sirtuin-1 (SIRT1) pathway and fatty acid metabolism are reported to be involved in influenza A virus (IAV) replication and IAV-pneumonia. Through a cell-based p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In a study of influenza A virus (IAV) -pneumonia, the activation of AMPK inhibited fatty acid biosynthesis and suppressed inflammatory progression and viral replication. 55 In the progression of SARS-COV-2 infection, phosphorylated and active forms of AMPK, AMPK substrates, and AMPK downregulated targets were suppressed. 56 Our pharmacology network-based study demonstrated a number of potential pharmacological targets, functions, and signalling pathways of CKZI in COVID-19 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of influenza A virus (IAV) -pneumonia, the activation of AMPK inhibited fatty acid biosynthesis and suppressed inflammatory progression and viral replication. 55 In the progression of SARS-COV-2 infection, phosphorylated and active forms of AMPK, AMPK substrates, and AMPK downregulated targets were suppressed. 56 Our pharmacology network-based study demonstrated a number of potential pharmacological targets, functions, and signalling pathways of CKZI in COVID-19 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For IAV (PR8), the mechanism of the anti-viral effect of emodin in A549 cells was to activate PPARα/γ and AMPK, decrease fatty acid biosynthesis, and increase intracellular ATP levels. In order to further prove that PPARα/γ and AMPK are the key proteins that inhibit PR8 replication, inhibitors were used, and it was found that the inhibitors of PPARα/γ and AMPK weakened the antiviral effect of emodin ( Bei et al, 2021 ). For H1N1, inhibiting the expression of hemagglutinin and neuraminidase, increasing the expression of interferon beta (IFN-β) through Toll-like receptor 9 (TLR9) are the key ways to inhibit the replication of it ( Lin CJ et al, 2015 ).…”
Section: Antiviral Activity Of Emodinmentioning
confidence: 99%
“…For H1N1, inhibiting the expression of hemagglutinin and neuraminidase, increasing the expression of interferon beta (IFN-β) through Toll-like receptor 9 (TLR9) are the key ways to inhibit the replication of it ( Lin CJ et al, 2015 ). In vivo studies, emodin also significantly protected mice from IAV infection and pneumonia ( Bei et al, 2021 ). Meanwhile, though experiments on A549 cells and C57BL/6J mice, DAI et al comprehensively explored the mechanism of emodin’s antiviral effect to H1N1.…”
Section: Antiviral Activity Of Emodinmentioning
confidence: 99%
See 1 more Smart Citation
“…Rheum officinale Baillon, Aloe vera and Polygonum cuspidatum have been demonstrated to display high inhibitory effects against IAV and their activity has been assigned to their phytoconstituents, including anthraquinones. Naturally occurring anthraquinones like emodin, aloe-emodin-8-O-β-D-glucopyranoside, chrysophanol-8-O-glucoside and emodin-1-O-β-D-glucopyranoside have been shown to significantly suppress IAV replication even at the lowest concentration of 3.125 μg/mL ( Bei et al, 2021 ). Aloe vera extract and its constituents, including aloe-emodin have been also reported to inhibit IAV.…”
Section: Antiviral Activity Of Anthraquinones Of Polygonaceae Rubiace...mentioning
confidence: 99%